Citrate is a circulatory exercise factor that promotes resilience to stress and has antidepressant properties in male mice - El Zoghby, Yara (2024)
Major Depressive Disorder (MDD) represents a leading cause of disability globally as estimated by the World Health Organization, with 320 million individuals afflicted. Conventional interventions such as pharmacotherapy and psychotherapy are commonly employed. However, environmental factors involving nutrition and physical activity have been demonstrated to influence MDD progression. Metabolites secreted during exercise, including beta-hydroxybutyrate and lactate, exhibit antidepressant properties and confer resilience against chronic stress. This study aimed to elucidate whether citrate, a Krebs cycle intermediate released into systemic circulation by exerting musculature, may serve as a novel prophylactic and therapeutic approach for MDD. Using a murine model of males and the Chronic Social Defeat Stress (CSDS) paradigm to induce depressive-like behaviors, we evaluated citrate's potential protective and antidepressant-like effects. Findings suggest citrate may promote resilience to stress and reverses depressive-like behaviors in male mice.